Particleboards from rice husk: A brief introduction to renewable materials of construction - Johnson, Anbu Clemensis, Dr.; Nordin, Yunus, Dato' Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/